The mediating role of peritraumatic stress in the relationship between childhood psychological maltreatment and optimism and pessimism among earthquake survivors in Turkey - Zafer Güney ÇAĞIŞ; İslam AKÇE; Izaddin Ahmad AZİZ; Amelia RIZZO; Gabriella NUCERA; Nicola BRAGAZZI; Lukasz SZARPAK; Francesco CHIRICO; Arash ZIAPOUR; Mehmet Emin ŞAKAR; Şoreş Hakı ÇELİK; Murat YILDIRIM (Journal of Health and Social Sciences)
Introduction: People encounter many events across their life span. However, some life experiences cause negative psychological outcomes. One of them is earthquakes. Therefore, in this study, it was aimed to examine the mediating role of peritraumatic distress in the relationship between childhood psychological maltreatment and optimism and pessimism among earthquake survivors. Methods: Using a snowball sampling technique with a cross-sectional research design, the sample comprised 311 adults who survived earthquake survivors in Turkey. Participants ranged in age between 18 and 61 years (mean age = 27.57±8.03). Of the participants, 231 (74.3%) were females and 80 (25.7%) were males, and they completed the Psychological Maltreatment Questionnaire–Short Form, Peritraumatic Distress Inventory, and Optimism and Pessimism Questionnaire. Results: The findings showed that childhood psychological maltreatment was positively related to peritraumatic distress and pessimism, and negatively related to optimism. Similarly, peritraumatic distress was positively related to pessimism and negatively related to optimism. More importantly, peritraumatic distress mediated the relationship between childhood psychological maltreatment and optimism and pessimism. These findings highlight the importance of addressing peritraumatic distress as an important factor in improving individuals’ perspectives on life. Discussion: Implementing tailored interventions to mitigate peritraumatic distress could lead to a more optimistic mindset and reduced levels of pessimism. By providing individuals with effective coping strategies and support systems, such interventions may empower them to overcome the challenges posed by stressful situations and cultivate a more positive outlook on life.